2003
DOI: 10.1016/s1470-0328(02)02976-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic restaging of borderline ovarian tumours: results of 30 cases initially presumed as stage IA borderline ovarian tumours

Abstract: Objectives To review our experience with the laparoscopic restaging procedure of presumed early stage borderline ovarian tumours. Design Retrospective study.Setting Cancer centre.Population Thirty patients with presumed stage I borderline ovarian tumours after limited initial surgery.Methods From April 1991 to May 2001, the patients were laparoscopically reassessed. The procedure involved peritoneal cytology, exploration of the peritoneal cavity, infracolic omentectomy, directed or random peritoneal biopsies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 11 publications
3
17
0
13
Order By: Relevance
“…These data are in full agreement with those of the only previous study to focus on laparoscopic restaging, in which Querleu et al [26] demonstrated its feasibility and acceptable morbidity rate.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These data are in full agreement with those of the only previous study to focus on laparoscopic restaging, in which Querleu et al [26] demonstrated its feasibility and acceptable morbidity rate.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, 16.6% of the women who underwent surgical restaging were upstaged, in keeping with previous reports (12-47%) [22][23][24][25][26]. Restaging had an impact on 21.4% of the women, including women with tumor persistence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, this strategy would result in most cases with borderline ovarian tumours and a very small number with benign tumours having systematic node dissection, and as there is no difference in recurrence or survival rate of patients with borderline ovarian tumours and nodal metastases, [30][31][32] it is generally considered that lymphadenectomy can be safely omitted in these patients. 33 However, the advantage of this strategy is that more cancer cases are identified at the time of surgery: cancer cases identified postoperatively on final histopathology that are not offered chemotherapy on the basis of high risk grade, stage or type, must choose between a second staging procedure 34,35 or accepting chemotherapy on the basis that lymph node metastases have not been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Borderline ovarian tumours, described in 1929 by Taylor [1], consist of a subgroup of ovarian tumours characterised by the presence of branching papillae, epithelial stratification, nuclear atypia, mitotic activity, and the absence of stromal invasion in the primary tumour [2]. These ovarian tumours comprise 7.5-15% of all epithelial ovarian neoplasms.…”
Section: Discussionmentioning
confidence: 99%